Lankesterella poeppigii n. sp. (Apicomplexa, Lankesterellidae) from Bufo poeppigii (Tschudi, 1845) from Peru - Paperna, Ilan (2009)
Lankesterella poeppigii n. sp. is described from Bufo poeppigii (Tschudi, 1845) from Peru. Merogony and oogony occur in the capillary endothelium and the macrophages in the liver, spleen and kidneys. Meronts are oval, 25,2–29,4 x 15,7–16,8 μm in size and yield 35–46 merozoites. Oocysts are 26,3–29,4 x 15,1–17,6 μm in size; sporozoites 9,2-9,8 x 4,2–5,0 μm in size, assemble in macrophages. Released 8,7–9,8 x 2,8–3,1 μm sporozoites enter erythrocytes. L. poeppigii is compared with Lankesterella petiti Lainson & Paperna, 1995 infecting Bufo marinus (Linnaeus, 1758) in Brazil. The above mentioned specific characters, added to differences in hosts and geographical location warrant the description of Lankesterella poeppigii from B. poeppigii as a new species.